The Granting of Family Card for Siri Marriage in Banda City: Perspective of Islamic Family Law - Daniela, Nadya Pratiwi; Hanapi, Agustin; Husnul, Muhammad; Fahri, Marjana (El-Usrah: Jurnal Hukum Keluarga, 2024)
Law No. 1 of 1974, as does the Compilation of Islamic Law, concerning marriage mandates the registration of every marriage to obtain legal validity such as a marriage certificate, which later becomes a requirement for making a family card. A family card is obtained if a marriage is registered in accordance with applicable laws and regulations. Siri (i.e., unregistered) marriage previously had various consequences, including children not having birth certificates, not having family cards, and, not being able to obtain their rights as husband and wife in the event of marital disputes. Therefore, marriage must be officially registered in order to obtain all the documents needed to create a family card. This will minimize the prevalence of siri marriage. However, the issuance of Minister of Home Affairs Regulation (PERMENDAGRI) No. 108 of 2019, which adds the status of unregistered marriage and unregistered divorce to the provision of family card, has allowed the registration of a family card without attaching a marriage certificate and accommodated providing family cards for unregistered marriages. On the one hand, having family cards is deemed necessary; yet, on the other hand, it is contrary to Law No. 1 of 1974 on Marriage. From a sociological point of view, it can have a negative impact on the increase of siri marriage as it no longer has any consequence at all. Thus, it is important to review the application of PERMENDAGRI No. 108 of 2019 sociologically from the perspective of Islamic family law using the theory of maslahah (benefit). This empirical study used the descriptive qualitative approach, which took place in Banda Aceh City. The study collected legal materials through document study. Sociologically, many negative effects have occurred on the issuance of family cards from the perspective of Islamic family law as well as the consequences of the implementation of PERMENDAGRI No. 108 of 2019 for women and children.